Accumulative pension schemes with various decremental factors - M. S. Al-Nator; S. V. Al-Nator; N. A. Olenchenko (Научный вестник МГТУ ГА)
We consider accumulative defined contribution pension schemes with a lump sum payment on retirement. These schemes differ in relation to inheritance and provide various decremental factors. A simulation model was developed to analyze the constructed schemes.